P–323 Ovarian response to stimulation according to endometrioma size, in women with deep infiltrating endometriosis – A comparative study. (6th August 2021) - Dahan, Y; Bourdon, M; Maignien, C; Patrat, C; Marcellin, L; Chapron, C; Santulli, P
Abstract: Study question: Does endometrioma (OMA) size affect the number of oocytes retrieved after ovarian stimulation (OS) in women with deep infiltrating endometriosis (DIE)? Summary answer: No significant difference in the number of oocytes retrieved was observed according to the endometrioma size. What is known already: Ovarian endometriosis lesions (OMA) per se and above all, the surgical excision, appears to result in a risk of alteration of the ovarian reserve. In vitro fertilization (IVF) is a validated therapeutic option to treat infertility related to endometriosis. Nevertheless, it has been described that the presence of OMA could have a detrimental impact on ovarian responsiveness to hyperstimulation involving mechanisms still unclear. Some recent studies suggest that the size of the OMA may be relevant and that there may be a threshold in cyst diameter above which ovarian responsiveness might be affected. Study design, size, duration: This was an observational study using data prospectively collected in a cohort of infertile women aged between 18 and 43 years presenting OMA associated with DIE lesions, between December 2012 and July 2019. Every patient underwent their first in vitro fecundation or intracytoplasmic sperm injection (IVF/ICSI) cycle. Included women were women with an adequate imaging work up with Transvaginal ultrasound and/or magnetic resonance imaging (TVUS/MRI) performed by senior radiologists before the beginning of the OS. Participants/materials, setting, methods: One hundred and eighty-two women were included in the study. Women were allocated in 5 groups according to the largest diameter of their ovarian endometriosis lesions: OMA < 2 cm, 2 cm ≤ OMA < 4 cm, 4 cm ≤ OMA < 6 cm, 6 cm ≤ OMA < 8 cm, OMA ≥ 8 cm. The main outcome was the number of oocytes retrieved. Main results and the role of chance: Mean age of the included women was 32.8 years. 96(52.7%) women had unilateral endometrioma and 86 (47.3%) had bilateral endometriomas. The mean OMA size was 3.63 cm for right ovary and 3.60 cm for left ovary. Considering the largest diameter of OMA retained, the mean size was 4.12 cm. Repartition among groups, according to the size of the largest OMA diameter was: OMA < 2cm group (n = 32); 2 £OMA< 4 cm (n = 70); 4 £OMA< 6 cm, (n = 37); 6 £OMA< 8 cm (n = 27); OMA8 cm (n = 16). Mean number of oocytes retrieved was not significantly different between groups (p = 0.635): 8.4±5.7 for OMA< 2 cm, 7.3 ± 5.4 for 2 cm≤OMA<4 cm, 6.6 ± 3.9 for 4 cm≤OMA< 6 cm, 8.6 ± 5.8 for 6 cm ≤OMA<8 cm and 7.1 ± 3.6 for OMA≥8 cm. Mean number of matures oocytes was also comparable between groups (p = 0.674). Clinical pregnancy rate and live birth rate was similar between groups (p = 0.798 and p = 0.913). No significant difference was found concerning the number of cancelled cycles between groups (p = 0.703). Limitations, reasons for caution: For almost half of the included women, endometriosis diagnosis was based on imaging technics, without histological proof of endometriosis. However, it was performed by specialized seniors radiologists. Wider implications of the findings: Our study suggests that whatever endometrioma size, OS can be benefit for women with endometrioma, even for largest ones, without the requirement of prior treatment to reduce their size Trial registration number: NA